Failure Analysis of NbVC Coating Formation onto AISI D2 Tool Steel during Thermo Reactive Diffusion by Pack Method - Izdada Rotaal Khamda; Fahmi Mubarok (Jurnal Teknik ITS, 2019)
Threads of metal fasteners can be created by thread rolling process using specific thread dies. The quality of the thread rolling die is determined by their wear-resistant and hardness properties. In order to increase the hardness and the wear resistance of the dies, thermo reactive diffusion can be applied. The TRD process is carried out by powder-pack method in a sealed steel container containing powder mixture of niobium and vanadium as master alloy, alumina (Al2O3) as inert filler and ammonium chloride (NH4Cl) as activator. The samples were covered with powder mixture and then heated in the electric resistance furnace at temperature of 950, 1000 and 1050 ˚C for 6 hours. Upon finishing the process, the sample is allowed to cool in the open air. The coating cross section was analyzed using optical microscope. The hardness measurement also performed on the same sample. XRD was utilized to investigate the coating chemical composition. The wear of the coatings are assessed using revolving tribological test under dry sliding condition. The XRD and microstructure test results did not find any niobium-vanadium carbide coating on AISI D2 substrate. In untreated and untreated specimens found chromium carbide (Cr7C3). Untreated specimen has hardness number of 277.8 HV. After TRD treatment, the hardness number is increase. For heating temperature variation of 950°C, 1000°C, and 1050°C have hardness number of 798.21HV, 787.3HV, 774.2HV respectively. The value of hardness rises due to the hardening of the AISI D2 specimen. The highest wear resistance owned by temperature variation of 950°C and the lowest wear resistance owned by the untreated specimen.